Evaluation of app-based serious gaming as a training method in teaching chest tube insertion to medical students: randomized controlled trial - Haubruck, Patrick; Nickel, Felix; Ober, Julian; Walker, Tilman; Bergdolt, Christian; Friedrich, Mirco; Müller, Beat P.; Forchheim, Franziska; Fischer, Christian; Schmidmaier, Gerhard; Tanner, Michael Christopher (Journal of medical internet research)
Background: The insertion of a chest tube should be as quick and accurate as possible to maximize the benefit and minimize possible complications for the patient. Therefore, comprehensive training and assessment before an emergency situation are essential for proficiency in chest tube insertion. Serious games have become more prevalent in surgical training because they enable students to study and train a procedure independently, and errors made have no effect on patients. However, up-to-date evidence regarding the effect of serious games on performance in procedures in emergency medicine remains scarce. Objective: The aim of this study was to investigate the serious gaming approach in teaching medical students an emergency procedure (chest tube insertion) using the app Touch Surgery and a modified objective structural assessment of technical skills (OSATS). Methods: In a prospective, rater-blinded, randomized controlled trial, medical students were randomized into two groups: intervention group or control group. Touch Surgery has been established as an innovative and cost-free app for mobile devices. The fully automatic software enables users to train medical procedures and afterwards self-assess their training effort. The module chest tube insertion teaches each key step in the insertion of a chest tube and enables users the meticulous application of a chest tube. In contrast, the module “Thoracocentesis” discusses a basic thoracocentesis. All students attended a lecture regarding chest tube insertion (regular curriculum) and afterwards received a Touch Surgery training lesson: intervention group used the module chest tube insertion and the control group used Thoracocentesis as control training. Participants’ performance in chest tube insertion on a porcine model was rated on-site via blinded face-to-face rating and via video recordings using a modified OSATS tool. Afterwards, every participant received an individual questionnaire for self-evaluation. Here, trainees gave information about their individual training level, as well as previous experiences, gender, and hobbies. Primary end point was operative performance during chest tube insertion by direct observance. Results: A total of 183 students enrolled, 116 students participated (63.4%), and 21 were excluded because of previous experiences in chest tube insertion. Students were randomized to the intervention group (49/95, 52%) and control group (46/95, 48%). The intervention group performed significantly better than the control group (Intervention group: 38.0 [I50=7.0] points; control group: 30.5 [I50=8.0] points; P<.001). The intervention group showed significantly improved economy of time and motion (P=.004), needed significantly less help (P<.001), and was more confident in handling of instruments (P<.001) than the control group. Conclusions: The results from this study show that serious games are a valid and effective tool in education of operative performance in chest tube insertion. We believe that serious games should be implemented in the surgical curriculum, as well as residency programs, in addition to traditional learning methods. Trial Registration: German Clinical Trials Register (DRKS) DRKS00009994; https://www.drks.de/drks_web/navigate.do?navigationId=trial.HTML&TRIAL_ID=DRKS00009994 (Archived by Webcite at http://www.webcitation.org/6ytWF1CWg) [J Med Internet Res 2018;20(5):e195]
Gesehen am 17.10.2019